Effect of synthetic antioxidants on storage stability of Calophyllum inophyllum biodiesel. (8th December 2014) - Rizwanul Fattah, I. M.; Masjuki, H. H.; Kalam, M.A.; Masum, B. M.
<x content-type="archive" xml:space="preserve">Abstract</x> Biofuels, especially biodiesels derived from renewable sources, are becoming increasingly important because of environmental and energy concerns. However, biodiesels composed of long chain unsaturated fatty acid esters are prone to oxidation. One such biodiesel is non-edible high acid value Calophyllum inophyllum oil-based biodiesel produced through a two-stage esterification process and one-stage transesterification process. In this study, the oxidation stability of biodiesel treated with three prominent antioxidants, namely pyrogallol, propyl gallate and tert-butylhydroxyquinone was evaluated. The induction period of biodiesel with or without antioxidant was measured according to the EN14112 standard using a Rancimat instrument. Antioxidants were added at 500 ppm, which in general improved the induction period. The samples were kept for 70 days and different properties that change during storage, namely induction period, density and kinematic viscosity were monitored. For all samples, oxidation stability decreased and kinematic viscosity increased because of the formation of oxidation products. Pyrogallol showed the best effect in retaining oxidation stability of Calophyllum inophyllum biodiesel.